2023
DOI: 10.1111/mcn.13503
|View full text |Cite
|
Sign up to set email alerts
|

Intrahousehold power inequalities and cooperation: Unpacking household responses to nutrition‐sensitive agriculture interventions in rural India

Abstract: Nutrition-sensitive agriculture (NSA) interventions offer a means to improve the dietary quality of rural, undernourished populations. Their effectiveness could be further increased by understanding how household dynamics enable or inhibit the uptake of NSA behaviours. We used a convergent parallel mixed-methods design to describe the links between household dynamics-specifically intrahousehold power inequalities and intrahousehold cooperation-and dietary quality and to explore whether household dynamics media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…In this review, some girls reported actively diminishing their agency during household decision-making, suggesting they acknowledge the benefits of acting in line with rather than challenging hierarchies in decision-making within households [ 49 , 85 , 90 ]. This supports other conceptualisations of household bargaining in South Asia which highlight that an absence of protest does not reflect an absence of questioning [ 13 , 128 ]. As household hierarchies frequently delayed or prevented care-seeking, we join others who call for an update to existing models which seek to understand care-seeking to incorporate the nuance of women’s decision-making capabilities [ 129 , 130 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this review, some girls reported actively diminishing their agency during household decision-making, suggesting they acknowledge the benefits of acting in line with rather than challenging hierarchies in decision-making within households [ 49 , 85 , 90 ]. This supports other conceptualisations of household bargaining in South Asia which highlight that an absence of protest does not reflect an absence of questioning [ 13 , 128 ]. As household hierarchies frequently delayed or prevented care-seeking, we join others who call for an update to existing models which seek to understand care-seeking to incorporate the nuance of women’s decision-making capabilities [ 129 , 130 ].…”
Section: Discussionsupporting
confidence: 86%
“…Early marriage is intimately connected with local cultural and gender norms which simultaneously drive the practice of early marriage and shape experiences [ 10 , 11 ]. In alignment with these norms, households tend to have hierarchies relating to gender and age, meaning young married girls are often discriminated against [ 12 , 13 ]. In South Asia, early marriage has been associated with interrupted education, restricted mobility outside of the home, social isolation, and limited decision-making [ 14 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A further benefit of the mobile platform was the successful engagement of whole families. Lack of family support is a key barrier to accessing nutrition interventions and adopting promoted behaviours in low and middle-income countries [ 32 ] and family support and cooperation were identified as important enabling factors in the UPAVAN trial [ 10 , 33 ]. Following this, m-UPAVAN actively promoted watching and listening with family members via phone messages and with facilitators after COVID-19 restrictions eased.…”
Section: Discussionmentioning
confidence: 99%